2023
DOI: 10.1088/1361-6528/acaf32
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion based 3D low complex runtime reconfigurable architecture design methodology of universal logic gate

Abstract: In this study, we introduce the area efficient low complex runtime reconfigurable architecture design methodology based on Skyrmion logic for universal logic gate (ULG) i.e., NOR / NAND implementation using micromagnetic simulations. We have modelled the two input 3D device structure using bilayer ferromagnet/heavy metal where the magnetic tunnel junctions (MTJs) inject and detect the input and output skyrmions by exploiting the input reversal mechanism. The implementation of NOR and NAND is performed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…demonstrated that VCMA can efficiently control the Néel vector in antiferromagnets with perpendicular anisotropy, enabling coherent excitation and manipulation of AFM order. The first-principles calculations further support these findings, with identified VCMA behavior in ultrathin FeRh/MgO bilayers and in materials like L1 0 -MnPd and MgO-capped MnPt AFM films. Therefore, the precise manipulation of the electric field emerges as a promising avenue for realizing a reconfigurable logic gate within AFM materials, offering flexibility in performing different logic functions. , Additionally, an essential aspect of skyrmion-based logic gates lies in the interaction between skyrmions themselves in AFM thin films, particularly the sky–sky topological repulsion, highlighting their tunability and potential for logic operations. Moreover, thoughtful geometric designs are one of the key mechanisms in reconfigurable skyrmion logic gates (RSL) as they grant the ability to exert control over the motion, interaction, and stability of skyrmions, all of which are critical elements for achieving the desired logic operations. , …”
Section: Introductionmentioning
confidence: 73%
“…demonstrated that VCMA can efficiently control the Néel vector in antiferromagnets with perpendicular anisotropy, enabling coherent excitation and manipulation of AFM order. The first-principles calculations further support these findings, with identified VCMA behavior in ultrathin FeRh/MgO bilayers and in materials like L1 0 -MnPd and MgO-capped MnPt AFM films. Therefore, the precise manipulation of the electric field emerges as a promising avenue for realizing a reconfigurable logic gate within AFM materials, offering flexibility in performing different logic functions. , Additionally, an essential aspect of skyrmion-based logic gates lies in the interaction between skyrmions themselves in AFM thin films, particularly the sky–sky topological repulsion, highlighting their tunability and potential for logic operations. Moreover, thoughtful geometric designs are one of the key mechanisms in reconfigurable skyrmion logic gates (RSL) as they grant the ability to exert control over the motion, interaction, and stability of skyrmions, all of which are critical elements for achieving the desired logic operations. , …”
Section: Introductionmentioning
confidence: 73%